(untitled) (Eureka Journal of Computing Science & Digital Innovation, 2026)
This article analyzes the causes, types and methods of resolving conflicts in professional activities. The article provides practical recommendations on reducing conflicts between employees and managers, increasing work efficiency in organizations and improving the working environment. The study provides examples based on local literature and the experience of Uzbekistan.